Endometrial carcinosarcoma in a young female with absence of established risk factors: a case report - Wei, Na; Bai, Shifeng; Kong, Donghui; Wang, Xiaomin; Mi, Xin (Frontiers in Oncology, 2025)
Endometrial carcinosarcoma is a rare, aggressive uterine malignancy, usually affecting postmenopausal women with recognised risk factors such as prolonged unopposed oestrogen exposure, tamoxifen use, pelvic irradiation, or high BMI. We report a 21-year-old Chinese woman with no known risk factors who presented with persistent vaginal bleeding, anaemia, and lower abdominal pain. Investigations showed microcytic hypochromic anaemia, elevated CA125, CA153, CA199, and Human Epididymis Protein 4, and pelvic MRI revealed a malignant endometrial lesion with vaginal involvement and lymphadenopathy. Biopsy confirmed carcinosarcoma with grade 3 endometrioid carcinoma as the epithelial component. Multidisciplinary review recommended extensive laparoscopic hysterectomy with bilateral adnexectomy, lymphadenectomy, and omentectomy, followed by six cycles of paclitaxel–carboplatin chemotherapy. Histology confirmed the diagnosis, and two-year follow-up showed no recurrence; a postoperative vesicovaginal fistula was surgically repaired. This atypical case in a young, underweight woman without established risk factors challenges current epidemiological assumptions and emphasises the importance of broad diagnostic consideration, timely referral, and comprehensive management.